(untitled) (Global Journal of Science Frontier Research, 2011)
Abstracts -Although Foraminiferid are very small members of marine and brackish water fauna they are often present in large numbers and constitute and important element of the meiofauna*. They possess hard parts in the form of tests (or Shells) which on death are preserved in the sediment and are therefore interest to geologists or researchers (Murray,J,W.1979). So, They could be remaining in the sedimentary layer as a proxy data. As because Present is the key to the Past. This research is an attempt to find out the Micro-environmental Change in the coastal Area of Bangladesh accompanying with a new technique, that is population analyze the marine micro faunas (Foraminiferid) in the bottom sediments. Laboratory analysis in the Geography and Environmental Studies, reveal that in the local Foraminiferid assemble zone of Chittagong coast (Shitakunda), they have been nonappearance. This is clear indications that present environmental condition for the sustainable micro fauna sp is not suitable. On the other hand It is indicating the hazardous coastal pollution which influences the sustainability of faunas themendously in this region.